The English in South Asian Contexts: Exploring Historical Development to Present Role in Education (Journal of Natural Language and Linguistics, 2024)
This article investigates the historical evolution and the current role of South Asian English (SAE) in the region’s education systems, with a particular focus on its function as a medium of instruction (EMI). By integrating both historical and contemporary insights, the article offers a detailed examination of how SAE has shaped educational practices. The methodology follows a systematic review process, involving the collection, analysis, and synthesis of scholarly works, government policies, and reports on English in South Asia. The findings highlight SAE’s dual role in acknowledging the region’s linguistic diversity while positioning English as a key tool for both local and global interactions. Tracing SAE’s origins to British colonial rule, the article explains how English was initially imposed for administrative purposes and later embraced by local elites. Over time, English became instrumental in governance, law, and education, often viewed as a neutral language to manage linguistic diversity. The rise of English-medium institutions further solidified its importance, resulting in a bilingual population fluent in both English and native languages. Today, SAE has evolved into a dynamic form of English, characterized by distinct local accents, idiomatic expressions, and cultural influences, giving rise to a unique linguistic identity in the region. The article also addresses current debates about the dominance of English in education, weighing the benefits of global connectivity against the need to preserve indigenous languages. It further explores pedagogical challenges and innovations in teaching SAE, particularly within multilingual classrooms. The article concludes by advocating for a balanced approach that incorporates SAE into a multilingual education system, promoting inclusivity and equitable learning opportunities throughout South Asia.